Responsiveness and interpretability of commonly used outcome assessments of mobility capacity in older hospital patients with cognitive spectrum disorders - Braun, Tobias (Health Qual Life Outcomes, 2021)
BACKGROUND: In older hospital patients with cognitive spectrum disorders (CSD), mobility should be monitored frequently with standardised and psychometrically sound measurement instruments. This study aimed to examine the responsiveness, minimal important change (MIC), floor effects and ceiling effects of commonly used outcome assessments of mobility capacity in older patients with dementia, delirium or other cognitive impairment. METHODS: In a cross-sectional study that included acute older hospital patients with CSD (study period: 02/2015–12/2015), the following mobility assessments were applied: de Morton Mobility Index (DEMMI), Hierarchical Assessment of Balance and Mobility (HABAM), Performance Oriented Mobility Assessment, Short Physical Performance Battery, 4-m gait speed test, 5-times chair rise test, 2-min walk test, Timed Up and Go test, Barthel Index mobility subscale, and Functional Ambulation Categories. These assessments were administered shorty after hospital admission (baseline) and repeated prior to discharge (follow-up). Global rating of mobility change scales and a clinical anchor of functional ambulation were used as external criteria to determine the area under the curve (AUC). Construct- and anchor-based approaches determined responsiveness. MIC values for each instrument were established from different anchor- and distribution-based approaches. RESULTS: Of the 63 participants (age range: 69–94 years) completing follow-up assessments with mild (Mini Mental State Examination: 19–24 points; 67%) and moderate (10–18 points; 33%) cognitive impairment, 25% were diagnosed with dementia alone, 13% with delirium alone, 11% with delirium superimposed on dementia and 51% with another cognitive impairment. The follow-up assessment was performed 10.8 ± 2.5 (range: 7–17) days on average after the baseline assessment. The DEMMI was the most responsive mobility assessment (all AUC > 0.7). For the other instruments, the data provided conflicting evidence of responsiveness, or evidence of no responsiveness. MIC values for each instrument varied depending on the method used for calculation. The DEMMI and HABAM were the only instruments without floor or ceiling effects. CONCLUSIONS: Most outcome assessments of mobility capacity seem insufficiently responsive to change in older hospital patients with CSD. The significant floor effects of most instruments further limit the monitoring of mobility alterations over time in this population. The DEMMI was the only instrument that was able to distinguish clinically important changes from measurement error. TRIAL REGISTRATION: German Clinical Trials Register (DRKS00005591). Registered February 2, 2015.